METHODOLOGICAL BENCHMARKS FOR PREPARING THE OLYMPIC TEAM FOR ECOLOGY - Gheorghe GÎNJU; Stela GÎNJU (Acta et Commentationes, Sciences of Education, 2019)
The current period is characterized by the presence of various ecological problems. A solution to the recovery of this situation is the ecological education of the young generation, which can be achieved through various ways. An efficient method is that of ecological projects. The article presents the advantages of this method, examples of good practices from the activity of ”M. Marinciuc” high school, which have in its list about 22 medals obtained at the Ecological Olympics using the method of ecological projects.